Implementation of advanced practice nursing for orthopaedic patients in the emergency care context – A study protocol for outcome studies. (15th January 2020) - Boman, Erika; Duvaland, Elisabeth; Gaarde, Kim; Leary, Alison; Fagerström, Lisbeth
Abstract: Aim: To evaluate the implementation of advanced practice nursing in emergency care in Norway for patients with orthopaedic injuries, including hip fractures. The outcomes relate to quality of care and patient trust. Design: A non‐inferiority study comparing an advanced practice nursing care model with a standard (physician‐led) care model. Methods: Data will be collected from patient records and through the Patient Trust Questionnaire, completed by patients. The data will be analysed by descriptive and inferential statistics. Funding for the research was granted in 2015 and the regional ethical committee approved the current study in February 2019. Discussion: In Norway and the other Nordic countries, advanced practice nursing is still in its infancy, especially in the emergency care context. This study will evaluate advanced practice nursing in this new context. Impact: The study will add to knowledge on the quality of care provided for orthopaedic patients with minor orthopaedic injuries or hip fractures as delivered by advanced practice nurses and physicians, respectively. It will also evaluate how well‐advanced practice nursing is accepted by patients in this new context. Abstract : 目的: 评价挪威急诊护理中对骨科伤患(包括髋部骨折患者)实施高级实践护理的情况。疗效与治疗质量和患者信任有关。 设计: 比较高级实践护理模式与标准(医师主导)护理模式的非劣效性研究。 方法: 从患者病历和患者填写的患者信任问卷中采集数据。通过描述性统计和推断性统计来分析采集的数据。于2015年拨款进行该研究, 并且区域伦理委员会于2019年2月批准了该研究。 讨论: 在挪威和其他北欧国家, 高级实践护理仍处于初级阶段, 特别是在急救护理方面。该研究将在这一新背景下, 对高级实践护理进行评估。 影响: 该研究将提高对高级实践护士和内科医生分别为骨科患者(轻微骨科损伤或髋部骨折)提供的治疗质量的认知, 还将评价患者在这一新背景下如何接受高水平实践护理。